The food substitutions bible : 8,000 substitutions for ingredients, equipment & techniques - Joachim, David (Robert Rose Inc., 2022)
"A beautifully illustrated, updated and expanded 3rd edition of the IACP Award winning Food Substitutions Bible Award-winning and bestselling author David Joachim has compiled creative and clear options that solve cooking dilemmas. With more than 8,000 alternative ingredients, equipment, and techniques covering emergency substitutions, time-saving substitutions, healthy substitutions, alternatives for hard-to-find ingredients, vegan and kosher alternatives, and ideas for varying the flavor of a dish in countless ways. You'll also find over 30 ingredient guides and measurements tables to help decipher things like choosing fresh chiles and pan size equivalents, plus 222 simple delicious recipes delicious recipes."--